Hubungan Agama dan Negara Dalam Perspektif Fiqh Siyasah - Firmansyah, Heri; Nur Fatimah (Tabayyun : Journal Of Islamic Studies, 2023)
This journal explores the intricate relationship between religion and state within the framework of Fiqh Siyasah, a branch of Islamic jurisprudence focusing on governance and politics. Religion, conceptualized as a set of obligations toward God, society, and oneself, serves as a guiding principle for human conduct across various aspects of life. Fiqh Siyasah emphasizes the crucial role of the state in implementing Islamic law on a broader societal scale. In the context of Fiqh Siyasah, the state transcends its administrative and political dimensions, emerging as an institution facilitating the application of Islamic principles in daily life. The leader, or imam, is entrusted with moral and spiritual responsibilities, not only to the community but also to Allah, requiring adherence to criteria such as justice, knowledge, and competence in managing the affairs of the people. Examining historical cases such as the Rashidun Caliphate provides an ideal model for understanding the balanced relationship between religion and state in Islam. The classical Islamic era demonstrates a symbiotic relationship, where religion and state mutually support and complement each other. However, contemporary challenges arise with the dynamics of globalization and diverse concepts of modern Islamic states.